Arrhythmogenic Right Ventricular Cardiomyopathy Diagnosed with 2020 International Criteria - Neelesh Damor; Nitin Modi; Atul Karande; Ashish Mishra; Sunil Sharma (Journal of the Indian Academy of Echocardiography & Cardiovascular Imaging)
Arrhythmogenic right ventricular cardiomyopathy (ARVC) is a rare cardiomyopathy. Early diagnosis is important to prevent mortality. They have a high risk of sudden cardiac death due to ventricular arrhythmia, which requires the implantation of a cardioverter-defibrillator. We describe the case of a cardiac arrest survivor with background electrocardiography (ECG) findings suggestive of ventricular tachycardia. The new 2020 international criteria for ARVC made it possible to easily detect such cases. We suspected right ventricular cardiomyopathy based on the patient’s history, ECG, and echocardiography findings, who later underwent cardiac magnetic resonance imaging. This was a “Definitive ARVC” case based on 2020 International criteria for ARVC. Clinicians should be aware of these criteria to detect such cases easily.